Popcorn thoughts: a podcast economy of film criticism - Blackburn, Hayley, author; Arthur, Tori, advisor; Humphrey, Michael, committee member; Wolfgang, David, committee member; Black, Ray, committee member; Marx, Nick, committee member (Colorado State University. Libraries, 2021)
This qualitative study questions how podcasters review films, engage with audiences, and contribute to film and media discourses. The literature exploring podcast cultures and film criticism had not intersected to a large extent, and this ethnographic inquiry into a case study of five podcast film critics provides an entry point for audio criticism scholarship. The research umbrella drew from film writing and critique cultures (Corrigan, 2015; McWhirter, 2016) and podcast analyses (Llinares, Fox, & Berry, 2018; Spinelli & Dann, 2019) to situate the patterns of discourse and production activities (Fairclough, 2003) within a framework of media sociology (Shoemaker & Reese, 2014). The research engaged with over 55 hours of content and various communication technologies in the winter of 2020/2021. The meso-level analysis considered the data from podcasts as a collective group to focus on the patterns across the audio critic culture (Kozinets, 2010). The findings reflect that audio critics can be further studied as a field of criticism as the collective group followed routines and enacted activities above individual and organizational levels of influence. Niches also frame the contributions of audio critics to the media and film discourse ecosystem as they extend film consumption rituals through discussion and provide a forum for participatory culture among their audiences.
Keywords: film criticism; podcast; critical cultural studies; pop culture; media studies